Keberagaman, Kesetaraan, dan Inklusi dalam Pendidikan Indonesia: Tinjauan Literatur Sistematis - Moh. Badrut Tamam; Josafat Gracia Ginting; Ahmad Rais Habib (Universitas Methodist Indonesia, 2025)
This study aims to synthesize current evidence on the practices, challenges, and potential levers of diversity, equity, and inclusion (DEI) in education in Indonesia. Using a Systematic Literature Review (SLR) approach, this article analyzes 34 articles selected from Scopus and ScienceDirect spanning the years 2020–2025. The selection process followed the PRISMA protocol, which involved searching for keywords related to DEI, multicultural education, disability inclusion, gender equality, and the digital divide. The results reveal five main themes: (1) DEI policies and landscapes in education; (2) multicultural education based on local wisdom that contributes to character building and social cohesion; (3) challenges in disability inclusion and gender equality; (4) the digital divide that impacts access to and quality of learning; and (5) educational institutional support that plays a crucial role in DEI implementation. The conclusions of this study emphasize the importance of strengthening teacher literacy and training on differentiated learning, equitable distribution of Information and Communication Technologies (ICT) infrastructure, and more inclusive and data-driven policies.